Pembelajaran Menulis Teks Karangan dengan Strategi Modeling pada Siswa Sekolah Dasar - Samsu Somadayo; Pamuti Pamuti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
The purpose of this study was to describe the abilities and skills of descriptive essay writing using modeling strategies in fourth-grade students of SD Negeri 81 in Hiri District, Ternate City. The design of the research method used is a descriptive qualitative research design. The data source in this study is information related to the results of students' teaching and learning activities after implementing modeling strategies to improve writing skills. Other data sources used are supporting documents that refer to systematic and standardized procedures to obtain the required data. The data for this research includes both process data and result data. Learning process data was obtained through observation, interviews, field notes, documentation studies, and recording during the learning process. Student essays result from student performance in descriptions writing obtained during the learning process. The awarding of final grades for student essays is based on signs of analysis of the assessment results of student essays, which include: (1) the suitability of the theme, topic, and content of the essay; (2) spelling usage and writing; (3) diction or word choice; (4) cohesiveness between sentences and between paragraphs; (5) neatness of writing; and (6) essay form. The study results relate to the implementation of learning to write descriptive essays using a modeling strategy whose stages include the pre-writing stage, the current stage of writing, and the post-writing stage. Thus, this research can reference elementary school teachers to use modeling strategies in descriptive essay writing.